Online Hate Speech: How discursive phenomena and rhetorical mechanisms influence negative emotions? - Marques, C.; Guerra, R.; Carvalho, P.; Sarroeira, R.; Fonseca, A.; Batista, F.; Ribeiro, R.; Moro, S. (XXXI Meeting of the Portuguese Association of Classification and Data Analysis (JOCLAD 2024), 2024)
This study aims to understand the psychosocial and linguistic characteristics associated with the direct (or explicit) or indirect (or implicit) manifestation of online hate speech (OHS), in the Portuguese online context. More specifically, this study aims to analyse how discursive phenomena underlying the expression of OHS relates with negative emotions, such as hate and anger. Furthermore, the proposed model analyses the role of diverse rhetorical mechanisms underlying the expression of OHS as mediator of the effects of discursive strategies on emotions. This study relies on a collection of 19500 annotated YouTube comments targeting racialized, Roma, migrant, and LGBTI+ communities. Structural equation modelling is used to estimate the model parameters. Comparisons between direct and indirect hate speech are conducted through multigroup analysis.